Sustainable energy transition and decision-making for enhancing the performance of building equipment in diverse climatic conditions - Seraj, Mohammad; Parvez, Mohd; Ahmad, Shafeeq; Khan, Osama (Green Technologies and Sustainability, 2023)
The utilization of renewable resources for energy generation holds paramount significance in ensuring substantial and enduring growth for every nation. Both developing and developed countries heavily rely on conventional energy sources like coal, petroleum, and natural gas in thermal power plants, resulting in significant environmental impact due to their emissions. This research culminates in the successful evaluation of alternative approaches to implement sustainable green structures using an innovative scientific technique. This research has effectively identified ten key challenges impeding operational efficiency in the construction industry. The application of the groundbreaking Analytical hierarchy process (AHP) technology facilitated the simultaneous ranking of the most optimal solutions. The precise assessment of numerous Energy Management equipment options for sustainable green buildings was achieved, highlighting the tool’s impartiality and neutrality in addressing Multiple Criteria Decision Making (MCDM) challenges. The ‘Roof-mounted Solar Photovoltaic (SPV)’ configuration consistently ranked first across all MCDM solution techniques examined in this study. This robust consensus underscores the significance of solar panels followed by biodiesel nanoparticles energy generation as the preferred choice. In conclusion, the impartiality of the tools used to address multi-criteria challenges in “greening building” projects empowers decision-makers within institutions to make informed investment choices. By considering the rankings generated by these tools, funding can be directed towards the most appropriate projects. Following prioritization, the alternatives are ranked as follows: Solar thermal setup > Installing sunshade devices > Light switches > Free cooling > Controlling the cooling & heating of spaces > Utilizing the chiller’s waste heat > Energy-efficient light bulbs > Electrical appliance energy efficiency ratings > Effective active space cooling solutions. •Energy generated from renewable resources is crucial for sustainable growth.•Conventional energy sources like coal and petroleum have a significant environmental impact.•Renewable energy will fulfil future energy demands in India due to diminishing fossil fuel reserves.•Using multi-dimensional modelling for ‘green building’ projects aids decision-making.